Non–animal collagens as new options for cosmetic formulation. (26th June 2015) - Peng, Y. Y.; Stoichevska, V.; Vashi, A.; Howell, L.; Fehr, F.; Dumsday, G. J.; Werkmeister, J. A.; Ramshaw, J. A. M.
Synopsis: Objective: To examine the potential of non‐animal collagens as a new option for cosmetic applications. Methods: Non‐animal collagens from three species, Streptococcus pyogenes, Solibacter usitatus and Methylobacterium sp 4‐46, have been expressed as recombinant proteins in Escherichia coli using a cold‐shock, pCold, expression system. The proteins were purified using either metal affinity chromatography or a simple process based on precipitation and proteolytic digestion of impurities, which is suitable for large‐scale production. Samples were examined using a range of analytical procedures. Results: Analyses by gel electrophoresis and mass spectrometry were used to examine the purity and integrity of the products. Circular dichroism spectroscopy showed stabilities around 38°C, and calculated pI values were from 5.4 to 8.6. UV‐visible light spectroscopy showed the clarity of collagen solutions. The collagens were soluble at low ionic strength between pH 5 and pH 8, but were less soluble under more acidic conditions. At lower pH, the insoluble material was well dispersed and did not form the fibrous associations and aggregates found with animal collagens. The materials were shown to be non‐cytotoxic to cells in culture. Conclusions: These novel, non‐animal collagens may be potential alternatives to animal collagens for inclusion in cosmetic formulations.